2020
DOI: 10.1177/2377960820970003
|View full text |Cite
|
Sign up to set email alerts
|

First Year’s Work Experiences of Foreign Educated Nurses Coming to Norway From Other European Countries

Abstract: Introduction Nurses educated in the European Union and European Economic Area are automatically given professional authorization to work in all member states, facilitating workforce mobility between countries. Along with many other European countries, Norway faces nursing shortages in healthcare. European Foreign Educated Nurses are often recruited to work in Norway by agencies or apply for work themselves. Aims To explore the experiences Foreign Educated Nurses from European Union and European Economic Area h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…An important point is the need to plan training according to the needs of nurses, which may imply the need for longer training. Another important issue is that the hiring of international nurses is generally a strategy used to solve the shortage of nurses, and this fact can shorten the orientation period for international nurses (Solum et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important point is the need to plan training according to the needs of nurses, which may imply the need for longer training. Another important issue is that the hiring of international nurses is generally a strategy used to solve the shortage of nurses, and this fact can shorten the orientation period for international nurses (Solum et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, good relations with colleagues and patients may facilitate international nurses' adaptation processes. Other factors, such as differences in nursing practice, the implementation of orientation programs, the possibility of gaining experience working abroad and job satisfaction also influence the professional integration of international nurses (Alanazi and Yates, 2022;Solum et al, 2020;Zakaria and Yusuf, 2022). It is important to discuss the experiences, backgrounds and perceptions of international nurses, especially because the topic is not sufficiently documented (Keshet and Popper-Giveon, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies [ 19 , 20 , 21 , 22 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] reported that international nurses felt distressed, confused, and humiliated by the discrimination they experienced while working. Participants reported incidents of discrimination including ‘patients displaying racist behaviour’, ‘refusal of care by international or Black nurses’ and ‘staff undermining the work of their international colleagues or drawing unfair conclusions about morale, motivation or character’ [ 26 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several other European studies focused on the labour market integration of medical healthcare professionals in terms of language acquisition, qualification recognition, and onboarding processes [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%